Implementation of Cash Dispense Accounting Systems of Civil Servants Payment in Regional Personnel and Human Resources Agency in Medan City - Cindy Shelina; Nurwani Nurwani (LPPM UIKA Bogor, 2023)
The government cannot implement the cash disbursement accounting system unless it increases its prudence in cash receipts and disbursements-related operations. This study's objective is to determine the applicability of the Cash Expenditure Accounting System, specifically with regard to the payroll of government officials. This qualitative study employs a descriptive methodology. In which analysis gathers, organizes, and maintains data to present an overview of a certain situation in order to form conclusions. The subject of this research was an employee of the Personnel and Human Resources Agency in Medan, Colombia, whose information was gathered via interviews and documentation. The findings of this study indicate that the accounting system for civil servant payroll cash disbursements at the Medan City Regional Personnel and Resources Agency has been implemented correctly, in an organized manner, and in accordance with the qualitative characteristics of systematic financial reports from the general treasurer who follows several procedures for disbursing payroll cash by referring to the current SOP (Standard Operating Procedure) for disbursing payroll cash.